Bacterial study of autopsy specimens - Somporn Srifeungfung (2018)
Autopsy reports were reviewed for the detection of infectious diseases at autopsy and to determine what extent an infectious process was involved in the patient's death. The present study was performed to analyze bacterial data of autopsy specimens in Siriraj Hospital during 1992-1999. Various autopsy specimens were cultured including heart blood, bronchus, lung, brain, cerebro-spinal fluid, pleural fluid, ascitic fluid, peritoneal fluid, liver, kidney, pericardial fluid, spleen and gall bladder. From 781 autopsy specimens 502 (64.28%) were positive for bacterial pathogens. The five most common bacterial pathogens isolated from the present study were nonfermentative gram-negative rods followed by Klebsiella pneumoniae, Salmonella serogroup E, Escerichia coli and Acinetobacter anitratus, respectively. The ante mortem diagnosis by clinicians was correct 56% regarding to retrospectively analysis of septicemia/septic shock versus autopsy culture from heart blood.